An exploratory corpus study of Malay word structures in school-aged children - Fakrul Razi, Fatin Syatirah; Jamaluddin, Saiful Adli; Wan Ahmad, Wan Aslynn Salwani (IIUM Press, 2025)
Introduction: Corpus-based research plays an essential role in understanding language structures relevant to education and clinical practice. This study provides an initial exploration of Malay word structures in school-aged children, focusing on grapheme-phoneme correspondences, syllable patterns, and inflectional morphemes. The findings aim to support linguistic research and inform speech-language pathology interventions. Methods: A descriptive analysis was conducted on a paediatric Malay corpus comprising the 1,000 most frequent words used by school-aged children. The words were analysed in terms of grapheme-phoneme relationships, syllable structures, and inflectional morphemes. Data were summarised descriptively. Results: The majority of words demonstrated direct grapheme-phoneme correspondence. Disyllabic words (50%) and CV syllable structures were the most frequent patterns identified (47%). Inflectional analysis revealed that root words (65%) predominated, with relatively fewer affixed or reduplicated forms. Conclusion: This preliminary study highlights key features of Malay word structures in school-aged children, confirming the language’s transparent orthography and prevalence of simple syllabic forms. These findings provide a foundation for future research and have potential applications in educational resources and speech-language pathology, particularly in developing assessment and intervention tools.